Driving Maqāṣid al-Shari’ah Performance in Islamic Banks: The Roles of Islamic Social Reporting, Intellectual Capital, and Sharia Governance - Arim Nasim; Elfina Qorina Binti Asbaruna; Juliana Juliana; Budi Supriatono Purnomo; Ropi Marlina; Muhamad Afif Sholahudin; Aam Slamet Rusydiana; Inomjon Qudratov (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2026)
This study aimed to examine the influence of Islamic Social Reporting (ISR) and Islamic Intellectual Capital (IIC) on the Maqasid Shariah Index (MSI) in Islamic banks, with Islamic Corporate Governance (ICG) acting as a moderating variable. A quantitative method was used to analyze secondary data from 19 Islamic commercial banks operating in Indonesia, Malaysia, and Saudi Arabia during the 2023–2024 period. ISR was measured through content analysis based on 39 disclosure indicators, while IIC was assessed using the iB-VAIC method. Furthermore, ICG was proxied by the frequency of meetings of the Board of Commissioners and Directors. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results show that ISR and IIC had a positive and significant effect on MSI, suggesting that ethical social disclosure and effective management of intellectual capital supported the achievement of maqasid shariah objectives in Islamic banking. ICG also showed strengthening roles by enhancing the relationships between ISR, IIC, and MSI. These results reflected the importance of integrating social responsibility, intellectual capital, and shariah-compliant governance to improve maqasid-based performance. In this study, important contributions were made to the body of knowledge by providing cross-country empirical evidence and offering a comprehensive framework for understanding maqasid-oriented performance in Islamic banking.